ACTing in Partnership to Accelerate Impact. (15th August 2018) - Harrison, Kate; Robinson, Joanna; Marks, Lauren; Blander, Jeffrey; McDermott, Peter
Abstract : Abstract: Partnership between funders plays a vital role in tackling the AIDS epidemic and can help partners deliver "more than the sum of their parts." But how do partnerships form? How is value leveraged and maximized? How can partnerships achieve policy change? This article addresses these questions through the example of the Accelerating Children's HIV/AIDS Treatment Initiative, an ambitious $200 million public private partnership with a goal of doubling the number of children living with HIV on treatment in 9 priority African countries over a 2-year period. It describes how the partnership formed between the US President's Emergency Plan for AIDS Relief (PEPFAR) and the Children's Investment Fund Foundation (CIFF), and the differing styles, vision, and resources each organization contributed. It also gives examples of policy influence at global level and policy change at national level. Finally, the article considers whether working in partnership was more or less effective than independent funding, with reflections on the value and challenges of collaboration.